Pengaruh Model Project Based Learning (PjBL) dalam Pembelajaran Menulis Teks Pidato Peserta Didik SMP - Ilmi, Hidayatun Nur; Harahap, Eddy Pahar; Purba, Andiopenta; Kamaruddin, Kamaruddin; Rustam, Rustam (Jurnal Ilmiah Dikdaya, 2024)
This research has a background in the low writing ability of junior high school students. The details of the problem in this study are: will the process of learning to write speech texts in classes using the Project Based Learning (PjBL) model give different results to classes using conventional learning models if it is carried out in class VIII students? The method used in this study is True Experimental Designs (actual experiments) with the design being the Pretest Posttest Control Group Design (pretest posttest control group design). The learning system control class uses the lecture method and the experimental class uses a project-based learning method. Based on the research results, the average pretest value for the control class was 45 and the experimental class was 53.3. Then the average value of the control class Posttest was 65.1 and the experimental class was 75.8. T test results The significance value of 2 tailed is 0,06 < 0.05, so there is a significant influence on the Project Based Learning (PjBL) model compared to the lecture model on the value of writing speech texts in class VIII students of junior high school.